Growth of Pb(Zr0.53Ti0.47)O3 thin films on (111) silicon substrates - O. Blanco (Superficies y vacío, 1999)
Pb(Zr0.53Ti0.47)O3 thin films were successfully grown on (111) silicon substrates by a high oxygen pressure RF sputtering technique which is used for the preparation of high Tc superconductors (HTS) thin films. Intermediate Ti and Al layers were evaporated on the (111) oxidized Si wafers and then subjected to an annealing processes in a furnace at 500ºC, 550ºC and 600ºC, for 5 hours before the ferroelectric thin film was deposited. The influence of the substrate preparation and deposition conditions on the structural properties of these films were examined by scanning electron microscopy (SEM) and x-ray diffraction (XRD) analysis